Maternal SARS-CoV-2 infection during pregnancy: possible impact on the infant - Morhart, Patrick; Mardin, Christian; Rauh, Manfred; Juengert, Joerg; Hammersen, Johanna; Kehl, Sven; Schuh, Wolfgang; Maier-Wohlfart, Sigrun; Hermes, Katharina; Neubert, Antje; Schneider, Michael; Hein, Alexander; et al. (European Journal of Pediatrics, 2021)
The risk and potential consequences of mother-to-child transmission of severe acute respiratory syndrome-coronavirus type 2 (SARS-CoV-2) during pregnancy are still a matter of debate. We studied the impact of SARS-CoV-2 infection on 56 complete households, including 27 newborns whose mothers were pregnant when exposed to the virus. Two PCR-confirmed perinatal SARS-CoV-2 transmissions with mild symptoms in affected neonates were recorded. In addition, we observed a severe eye malformation (unilateral microphthalmia, optic nerve hypoplasia, and congenital retinopathy) associated with maternal SARS-CoV-2 infection in weeks 5 and 6 of embryonic development. This embryopathy could not be explained by other infectious agents, genetic factors, drug use, or maternal disease during pregnancy. Eight other women with a history of SARS-CoV-2 infection prior to gestational week 12, however, delivered healthy infants. Conclusion: The repeated occurrence of mother-to-child transmission in our cohort with risks that remain incompletely understood, such as long-term effects and the possibility of an embryopathy, should sensitize researchers and stimulate further studies as well as support COVID-19 vaccination recommendations for pregnant women. Trial registration number: NCT04741412. Date of registration: November 18, 2020What is Known:•Materno-fetal transmission of severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) during pregnancy has rarely been reported so far, but was demonstrated in isolated cases.What is New:•In a study of complete households with documented SARS-CoV-2 infection, including a cohort of pregnant women, we observed perinatal coronavirus transmission at a higher frequency than expected.•We also describe a newborn boy with an eye malformation reminiscent of rubella embryopathy but associated with early gestation SARS-CoV-2 infection of his mother.•A coronavirus-related embryopathy, reported here for the first time, is a finding that requires further investigation.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Case report; Coronavirus; Embryopathy; Malformation; Materno-fetal transmission